Kemanfaatan Hukum Dalam Penerapan Diversi Dan Keadilan Restoratif Dalam Perkara Pidana Anak - Achmad Maulana Fakhri; Roravianita Roravianita; Jenifer Otnie; Reza Fahrezi; Herli Antoni (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
This research aims to analyze the application of diversion and restorative justice in criminal cases committed by minors. The application of diversion is examined in more depth about the obligation of every law enforcer to carry out a series of diversion processes in the police, prosecutor's office and up to the court. The implementation of diversion is something that must be done without exception in accordance with the provisions of Law No. 11/2012 concerning the Juvenile Criminal Justice System. The application of restorative justice seeks a benchmark for the extent to which it can be implemented by taking into account the authority possessed by the public prosecutor when the diversion process is not achieved and when the criminal case has entered the criminal justice process. The application of the termination of prosecution must be based on the applicable provisions and conditions contained in the Attorney General's Decree No. 15 of 2020. After conducting research on diversion and restorative justice, the only legal benefit of juvenile criminal cases is through the provision of punishment for a child who is a perpetrator of a criminal offense in accordance with the provisions of the laws and regulations concerning the juvenile criminal justice system.